A novel general multiple-base data embedding algorithm - Chen, Wei-Sung; Liao, Yi-Kai; Lin, Yun-Te; Wang, Chung-Ming (Information sciences, 2016)
•Presenting a GMB algorithm to conceal secret bits in n pixels with least distortion.•GMB offers greater flexibility providing large payloads or high image quality.•Introducing four binary conversion schemes to carry an extra bit for concealment.•Deriving mathematical expressions to predict expected payloads and image quality.•GMB scheme outperforms ten current state-of-the-art competitors. This paper presents a general multiple-base (GMB) data embedding algorithm to conceal a serial secret bit stream equivalent to an M-ary secret digit in a pixel-cluster consisting of n pixels, where M is automatically determined by the initial input (n, F) given by the end user. Through the change of two parameters, n and M, the proposed algorithm offers a multiple-purpose message embedding style to produce a high quality embedded image or provide a large embedding payload. Inspired by a single base (SB) data embedding approach, this study first introduces a multiple-base (MB) scheme which adopts an n-tuple optimal base vector (OBV) to conceal a secret M-ary digit with minimal pixel distortion, where M is the product of all vector components in the OBV. This study extends the MB scheme to develop the GMB algorithm, which supports a serial secret bit stream as a secret message. Four binary to M-ary conversion schemes are introduced, allowing the GMB algorithm to carry an extra secret bit per pixel-cluster, offering a larger payload without increasing the pixel distortion caused by data embedding. The proposed algorithm is analyzed, and mathematical expressions are derived so that prior to a real message embedding, it is possible to predict the expected payloads and the corresponding image quality. Finally, we extend the GMB algorithm to support content-adaptive data embedding. To the best of the authors' knowledge, the proposed algorithm is the first multiple-purpose data embedding technique, providing greater flexibility and offering large payloads or high image quality. Experimental results demonstrate that the proposed scheme outperforms current state-of-the-art competitors.